2010
DOI: 10.1007/s11738-009-0451-8
|View full text |Cite
|
Sign up to set email alerts
|

What happens in plant molecular responses to cold stress?

Abstract: Low temperature is one of the major abiotic stresses limiting the productivity and the geographical distribution of many important crops. Many plants increase in freezing tolerance in response to low temperatures. This phenomenon needs a vast reprogramming of gene expression which results in the adjusted metabolic-structural alterations. However, the efficient adjustments are dependent on proper cold signal transduction. The first stage is cold stress signal perception which is carried out by different pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(115 citation statements)
references
References 121 publications
2
107
0
Order By: Relevance
“…This more fluid state of cell membranes helps to protect cells under the effect of low-temperature stress through maintaining the cell shape and preventing cellular component from water loss. Moreover, the rigidity of membrane could reduce cells collapsing during extracellular freezing by creating a negative pressure in the cells (Rajashekar & Lafta 1996;Heidarvand & Maali Amiri 2010). Takahashi et al (2013) reported that the alternation of plasma membrane composition and function is one of the most important mechanisms of plant cold tolerance.…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…This more fluid state of cell membranes helps to protect cells under the effect of low-temperature stress through maintaining the cell shape and preventing cellular component from water loss. Moreover, the rigidity of membrane could reduce cells collapsing during extracellular freezing by creating a negative pressure in the cells (Rajashekar & Lafta 1996;Heidarvand & Maali Amiri 2010). Takahashi et al (2013) reported that the alternation of plasma membrane composition and function is one of the most important mechanisms of plant cold tolerance.…”
Section: Cold Acclimation and Frost Stress Tolerancementioning
confidence: 99%
“…Fowler and Thomashow (2002) reported that cold acclimation activates different gene expression pathways which in turn means that cold-induced genes could be members of more than one cold regulon. However, it should be mentioned that plant response to abiotic stresses is mediated by a common group of reactions, cooperatively known as signal transduction (Heidarvand & Maali Amiri 2010). Therefore, plant response to low temperature goes through specific process starting by cell recognition of low temperature (sensing) followed by the signaling process in order to induce the cold-responsive genes resulting in an increase in plant cold tolerance (Denesik 2007).…”
Section: Gene Expression Induction In Response To Low Temperaturementioning
confidence: 99%
“…1 The cold acclimation includes complex cellular and biochemical changes such as altered membrane composition, accumulation of soluble sugars, proline, as well as the production of antifreeze proteins. [2][3][4][5] In winter cereals 6 and in Arabidopsis thaliana, [7][8] the cold acclimation was shown to result in an increased photosynthetic activity. The capacity to acclimate to low temperature largely deviates in accessions of Arabidopsis thaliana originating from warm and 3 arnd G. heyer 3 and Ladislav Nedbal…”
Section: Introductionmentioning
confidence: 99%
“…Based on the stress nature and severity, multiple sensors are expected to perceive various types of osmotic stresses (Xiong and Zhu, 2002;Kacperska, 2004). Cold sensors may be involved in the detection of membrane physical state/fluidity, changes in cytoskeleton, and cell wall structure (Heidarvand and Amiri, 2010). Drought sensors may be associated with membrane dehydration (Mahajan and Tuteja, 2005) and turgor pressure (Reiser et al, 2003).…”
Section: Stress Sensorsmentioning
confidence: 99%